Policy analysis in sport: a review of mainstream meso-level frameworks and developing more sustainable policy for grassroots sport - Charles Mountifield (Frontiers in Sports and Active Living)
This paper reviews some mainstream meso-level policy analysis frameworks widely applied in sport. There is, however, an absence of consensus for an established framework for analysing sport policy in general and, instead, techniques emanating from other fields of study have been relied upon. The resultant approach to sport policy analysis is inconsistent, multidimensional, and lacks unanimity, leading to calls for a sport-specific framework. This research outlines how meso-level frameworks have been applied in sport policy and issues linked to sustainability from a grassroots policy perspective. A narrative literature review provides an overview of prevalent approaches, namely Institutional Analysis, the Multiple Streams Framework, Policy Network Theory, and the Advocacy Coalition Framework. Aspects of applying these models to sport policy—including some key advantages and disadvantages—are outlined, especially the issue of conventional top-policy processes, the impact on policy implementers at grassroots level, and the potential for bottom-up policy influence. The article examines the four frameworks in the context of praxes in sport, noting the overall importance of a meso-level approach to sport policy analysis and that arriving at an holistic and inclusive accord has merit.